Synthesis, characterization and optimization of cerium and calcium oxides based catalysts towards carbon dioxide methanation reaction - Iqbal, Malik Muhammad Asif (2020)
Novel trimetal-oxide (Ru/Fe/Ce) supported on γ-Al2O3 catalysts were synthesized by simple impregnation method. The conversion of CO2 to CH4 was optimized using response surface methodology (RSM) based on the amount of catalyst loading, calcination temperatures and catalyst dosages. In addition, stability, reliability, robustness, reproducibility, and regeneration testing were also investigated. Superior catalytic performance was obtained using catalyst with ruthenium content of 5 wt% loading, iron content of 10 wt% loading and cerium content of 85 wt% loading which was calcined at 1000°C for 5 h. The CO2 conversion achieved 97.2% at 275°C with CH4 formation of 93.5%. The Ru/Fe/Ce (5:10:85)/γ-Al2O3 catalyst exhibits excellent catalytic stability up to 65 h. CO2-TPD results revealed this catalyst possesses medium-strength basic sites while TPR study revealed the catalyst exhibits best reduction pre-treatment at >250°C. Meanwhile, the BET analysis illustrated the catalyst possesses a mesoporous structure. XRD revealed the transformation of cubic Al2O3 calcined at 1000°C to rhombohedral at 1100°C. TEM micrographs revealed the d-spacing value is in accordance with XRD analyses. FESEM micrographs displayed the catalyst surface is covered with small, dispersed spherical particles. EDX mapping profile showed good distributions of Ce, Fe, and Ru on the catalyst surface. The physicochemical analyses have shown that the active sites of the potential catalyst Ru/Fe/Ce (5:10:85)/γ-Al2O3 are RuO2 (t), Fe2O3 (r), Al2O3 (c), Al2O3 (r) and CeO2 (c) with a particle size <10 nm. The mechanistic studies have shown that CO2 methanation occurs via the adsorption of CO2 on surface of ceria and iron oxide, and then stepwise hydrogenation leading to CH4 formation through carboxylate intermediate by the hydrogen spilled over from Ru surface. As a result, dissociated hydrogen over ruthenium reacts with surface carbon, leading to formation of *CH intermediate, which subsequently hydrogenated to produce *CH2, *CH3 and finally to the desired product methane. The Ru/Fe/Ca (5:25:70)/γ-Al2O3 catalyst calcined at 1000°C gave a maximum conversion of 85.59% CO2 with CH4 formation of 79.58% at a reaction temperature of 300°C which was less as compared to the potential catalyst Ru/Fe/Ce (5:10:85)/γ-Al2O3.